2007
DOI: 10.1007/s00108-007-1800-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatische 32-jährige Raucherin mit persistierender Lymphozytose

Abstract: A 32 year old female smoker (20 pack years) presented with an asymptomatic lymphocytosis of 13,000/nl and splenomegaly. The patient's blood smear showed an absolute lymphocytosis with 65% atypical lymphocytes. A total of 1% of the lymphocytes were bilobulated. Bone marrow histology and immunphenotyping of blood and bone marrow excluded leukemia and non-Hodgkin's lymphoma. IgH-CDR-3 PCR analysis revealed a polyclonal pattern. In summary, a persistent polyclonal B-cell-lymphocytosis (PPBL) was diagnosed. The exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Cigarette smoke condensation inhibits an early step in the caspase cascade to prevent apoptosis and induces necrosis 10) . It has been reported that a 32-year-old female smoker presented with absolute lymphocytosis with 65% atypical lymphocytes and a total of 1% bilobulated lymphocytes 11) , which was partly due to a defect in lymphocyte apoptosis signaling 11) . The PBMCs of smokers exhibited a delay in cell proliferation kinetics and a decrease in replication index compared with nonsmokers 12) .…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke condensation inhibits an early step in the caspase cascade to prevent apoptosis and induces necrosis 10) . It has been reported that a 32-year-old female smoker presented with absolute lymphocytosis with 65% atypical lymphocytes and a total of 1% bilobulated lymphocytes 11) , which was partly due to a defect in lymphocyte apoptosis signaling 11) . The PBMCs of smokers exhibited a delay in cell proliferation kinetics and a decrease in replication index compared with nonsmokers 12) .…”
Section: Discussionmentioning
confidence: 99%